Prevalence of Antimicrobial-Resistant Pathogens in Canadian Hospitals: Results of the Canadian Ward Surveillance Study (CANWARD 2008) - Zhanel, George G. (American Society for Microbiology (ASM), 2010)
A total of 5,282 bacterial isolates obtained between 1 January and 31 December 31 2008, inclusive, from patients in 10 hospitals across Canada as part of the Canadian Ward Surveillance Study (CANWARD 2008) underwent susceptibility testing. The 10 most common organisms, representing 78.8% of all clinical specimens, were as follows: Escherichia coli (21.4%), methicillin-susceptible Staphylococcus aureus (MSSA; 13.9%), Streptococcus pneumoniae (10.3%), Pseudomonas aeruginosa (7.1%), Klebsiella pneumoniae (6.0%), coagulase-negative staphylococci/Staphylococcus epidermidis (5.4%), methicillin-resistant S. aureus (MRSA; 5.1%), Haemophilus influenzae (4.1%), Enterococcus spp. (3.3%), Enterobacter cloacae (2.2%). MRSA comprised 27.0% (272/1,007) of all S. aureus isolates (genotypically, 68.8% of MRSA were health care associated [HA-MRSA] and 27.6% were community associated [CA-MRSA]). Extended-spectrum β-lactamase (ESBL)-producing E. coli occurred in 4.9% of E. coli isolates. The CTX-M type was the predominant ESBL, with CTX-M-15 the most prevalent genotype. MRSA demonstrated no resistance to ceftobiprole, daptomycin, linezolid, telavancin, tigecycline, or vancomycin (0.4% intermediate intermediate resistance). E. coli demonstrated no resistance to ertapenem, meropenem, or tigecycline. Resistance rates with P. aeruginosa were as follows: colistin (polymyxin E), 0.8%; amikacin, 3.5%; cefepime, 7.2%; gentamicin, 12.3%; fluoroquinolones, 19.0 to 24.1%; meropenem, 5.6%; piperacillin-tazobactam, 8.0%. A multidrug-resistant (MDR) phenotype occurred frequently in P. aeruginosa (5.9%) but uncommonly in E. coli (1.2%) and K. pneumoniae (0.9%). In conclusion, E. coli, S. aureus (MSSA and MRSA), P. aeruginosa, S. pneumoniae, K. pneumoniae, H. influenzae, and Enterococcus spp. are the most common isolates recovered from clinical specimens in Canadian hospitals. The prevalence of MRSA was 27.0% (of which genotypically 27.6% were CA-MRSA), while ESBL-producing E. coli occurred in 4.9% of isolates. An MDR phenotype was common in P. aeruginosa.